Case Report: Progressive interstitial lung disease secondary to Sjögren’s disease in a patient with inclusion body myositis complicated by dysphagia—a multidisciplinary approach and therapeutic challenges - Cocchiara, Emanuele; Cozzini, Francesca; Chiapparoli, Ilaria; Falco, Francesco; Bajocchi, Gianluigi; Salvarani, Carlo; Manfredi, Andreina (Frontiers in Medicine, 2025)
We present the case of a 78-year-old man with a complex overlap of inclusion body myositis (IBM) and Sjögren’s disease (SjD), complicated by interstitial lung disease (ILD) and esophageal dysfunction. The patient’s neuromuscular decline was managed with periodic intravenous immunoglobulins (IVIG), while his progressive ILD required a combined immunosuppressive and antifibrotic regimen, including prednisone. This case underscores the diagnostic and therapeutic challenges in managing autoimmune overlap syndromes, particularly the rare coexistence of IBM and SjD-related ILD. We highlight the rationale behind the treatment strategy and the importance of a tailored, multidisciplinary approach in addressing both muscular and pulmonary manifestations.